2011
DOI: 10.2147/opth.s23086
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Goldmann and Pascal tonometry in relation to corneal hysteresis and central corneal thickness in nonglaucomatous eyes

Abstract: Objective:To compare measurements obtained by Goldmann applanation tonometry (GAT) and Pascal dynamic contour tonometry (DCT), and to study their relationship to corneal thickness and biomechanical properties in nonglaucomatous eyes.Methods:This is a prospective and randomized study of 200 eyes from 200 non-glaucomatous subjects who underwent intraocular pressure (IOP) measurements by GAT and DCT. The two methods were compared and assessed for agreement by means of the Bland–Altman plot. Central corneal thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 56 publications
2
13
0
1
Order By: Relevance
“…In contrast to GAT, the Pascal tonometry provides direct transcorneal IOP measurements independent of central corneal thickness, corneal curvature, and is less prone to examiner dependant measurement bias. [11][12][13][14][15] As expected, Pascal readings in our study were in mean 2-4 mmHg higher than GAT readings. [16][17][18][19] However, even after correcting for this well described fact, Pascal readings detected IOP elevations more sensitive, especially at IOP values ‡ 25 mmHg Similar to the results of the GENEVA study, we found a peak of IOP elevation 2 months after dexamethasone 0.7 mg injections.…”
Section: Intraocular Pressuresupporting
confidence: 85%
“…In contrast to GAT, the Pascal tonometry provides direct transcorneal IOP measurements independent of central corneal thickness, corneal curvature, and is less prone to examiner dependant measurement bias. [11][12][13][14][15] As expected, Pascal readings in our study were in mean 2-4 mmHg higher than GAT readings. [16][17][18][19] However, even after correcting for this well described fact, Pascal readings detected IOP elevations more sensitive, especially at IOP values ‡ 25 mmHg Similar to the results of the GENEVA study, we found a peak of IOP elevation 2 months after dexamethasone 0.7 mg injections.…”
Section: Intraocular Pressuresupporting
confidence: 85%
“…38 However, other studies have described a weak but significant relationship between GAT IOP and CH and this could confound the determination of the independent role of CH as a risk factor for progression. 39, 4042 It should be noted, however, that even though part of the predictive effect of CH might be explained by its effect on GAT measurements, CH would still be a valid and relevant predictive factor, as shown by the model presented in our study. Further studies should clarify the role of CH as a true independent risk factor for glaucoma progression by evaluating its role in multivariable models including cornealindependent IOP measurements.…”
Section: Discussionmentioning
confidence: 50%
“…DCT is an alternative way to measure IOP, and is based on a completely new physical principle that does not distort the corneal anatomy 16. Therefore, DCT seems to be less affected by factors such as corneal thickness and hysteresis when compared with GAT 25. In our study, the difference between mean measurements taken on DCT and GAT was 1.7 mmHg.…”
Section: Discussionmentioning
confidence: 51%